From Symmetry Breaking to Unraveling the Origin of the Chirality of Ligated Au13Cu2 Nanoclusters. Issue 13 (23rd February 2018) - Deng, Guocheng; Malola, Sami; Yan, Juanzhu; Han, Yingzi; Yuan, Peng; Zhao, Chaowei; Yuan, Xiting; Lin, Shuichao; Tang, Zichao; Teo, Boon K.; Häkkinen, Hannu; Zheng, Nanfeng
Abstract: A general method, using mixed ligands (here diphosphines and thiolates) is devised to turn an achiral metal cluster, Au13 Cu2, into an enantiomeric pair by breaking (lowering) the overall molecular symmetry with the ligands. Using an achiral diphosphine, a racemic [Au13 Cu2 (DPPP)3 (SPy)6 ] + was prepared which crystallizes in centrosymmetric space groups. Using chiral diphosphines, enantioselective synthesis of an optically pure, enantiomeric pair of [Au13 Cu2 ((2r, 4r)/(2s, 4s)‐BDPP)3 (SPy)6 ] + was achieved in one pot. Their circular dichroism (CD) spectra give perfect mirror images in the range of 250–500 nm with maximum anisotropy factors of 1.2×10 −3 . DFT calculations provided good correlations with the observed CD spectra of the enantiomers and, more importantly, revealed the origin of the chirality. Racemization studies show high stability (no racemization at 70 °C) of these chiral nanoclusters, which hold great promise in applications such as asymmetry catalysis. Abstract : Meet me at the symmetry gates : Using mixed ligands, diphosphines and pyridinethiol, an achiral metal cluster, Au13 Cu2, can be turned into an enantiomeric pair by breaking the reflection and inversion symmetries. Chiral diphosphines allow one‐pot enantioselective synthesis of enantiomers with 100 % optical purity. Temperature‐dependent racemization studies showed high chirality stability (up to 70 °C). DFT calculations revealed the origin of the chirality.